Violence against health professionals and facilities in China: Evidence from criminal litigation records. (October 2019) - Li, Niying; Wang, Zhan; Dear, Keith
Abstract: Objectives: This study aims to extend the current understanding of violence against health professionals and facilities in China, with data from an authoritative, national-representative, but under-researched data source – litigation records, and discuss implications for developing violence prevention strategies. Design: We collected all legal cases relevant to violence against health professionals and facilities from criminal ligation records released by the Supreme Court of China from 2010 to 2016. Main outcome measures: (i) Characteristics of perpetrators: gender, age, education, occupation, history of mental illness and alcohol; (ii) characteristics of victims: medical specialization, location, type of violence; (iii) outcome of treatment. Results: 140 cases were collected for analysis. Beating, pushing, verbal abuse, threatening, burning mock paper money, placing a corpse in the hospital, hanging banners, blocking hospital gates and doors, and smashing hospital property were the most frequently reported types of violence. Specifically following patient deaths, the interval between a patient's death and violence by the patient's families and friends was short, with 51% happening on the same day. Conclusions: Our study provides a comprehensive overview of violence against health professionals and facilities in China, which can be used to inform the development of prevention strategies. Highlights: Violence occurred across all types of facilities. Cases include physical, psychological violence and medical disturbance. Following patient death, violence was initiated by patients' families quickly.